The effectiveness of the Dutch Meaningful Roles program in children: a study protocol for a cluster randomized controlled study - Amanda W. G. van Loon; Tessa M. L. Kaufman (BMC, 2023)
Abstract Background A positive, prosocial classroom climate is associated with improved social competence and academic achievement, as well as with decreased internalizing problems and antisocial behavior in children. It is expected that motivation to behave prosocially is needed to achieve a prosocial climate in the classroom, and that such motivation can be enhanced through three components of self-determination theory (SDT): competence, relatedness, and autonomy. The goal of this protocol is to describe the design of a study aiming to evaluate the effectiveness of a classroom-based program based on SDT components promoting a prosocial classroom climate. Methods A cluster randomized controlled trial (RCT) will be conducted to examine the effectiveness of the classroom-based program Meaningful Roles, aiming to improve prosocial classroom climate through increasing children's intrinsic prosocial motivation, stimulated by increasing social autonomy, social competence, and social relatedness. A multi-informant (i.e., children, teachers, and school leaders) and multi-method (i.e., questionnaires and focus groups) approach will be used to assess primary outcomes (i.e., prosocial behavior, intrinsic (prosocial) motivation, social autonomy, social competence, and social relatedness) and secondary outcomes (i.e., school wellbeing, social position, bullying, victimization, and civic skills), as well as moderators (i.e., working elements, child, teacher, school, and program characteristics, and program integrity). Discussion The current study will provide information on the effectiveness of a classroom-based program promoting a prosocial classroom climate. It is of crucial importance that the school environment can provide a positive, prosocial classroom climate in which children feel safe and can achieve optimal social and academic competence and wellbeing. Trial registration ClinicalTrials ( NCT05891067 ).